2011
DOI: 10.1007/s10447-011-9127-3
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Eating Cognitions as Predictors of Attitudes toward Seeking Professional Psychological Services

Abstract: The present study investigated whether young adults' disordered eating cognitions predicted attitudes toward seeking professional psychological services. Two hundred and eighty three 18-to 24-year-old undergraduate students completed a survey package that included measures of disordered eating cognitions and help-seeking attitudes. Hierarchical regression analyses revealed that greater disordered eating cognitions uniquely predicted lower degrees of favorable help-seeking attitudes overall, lower stigma tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Tolerance of mental health treatment stigma was measured with the Stigma Tolerance subscale of the Attitudes Toward Seeking Professional Psychological Help Scale (ATSPPH) . This 5‐item subscale has demonstrated acceptable internal consistency among an ethnically diverse sample of female undergraduates …”
Section: Methodsmentioning
confidence: 99%
“…Tolerance of mental health treatment stigma was measured with the Stigma Tolerance subscale of the Attitudes Toward Seeking Professional Psychological Help Scale (ATSPPH) . This 5‐item subscale has demonstrated acceptable internal consistency among an ethnically diverse sample of female undergraduates …”
Section: Methodsmentioning
confidence: 99%
“…Indeed, a nationally representative study of adolescents found that in addition to greater symptom severity (particularly restricting and purging severity), individuals with greater role impairment were more likely to seek treatment (Forrest et al, ). Disordered eating cognitions have also been shown to negatively predict treatment‐seeking attitudes; namely, higher levels of disordered eating cognitions are associated with less favorable attitudes toward treatment seeking (Dotson, Masuda, & Cohen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging adults In one longitudinal and two cross-sectional studies with emerging adult samples, it was similarly found that males and ethnic or racial minorities were less likely to seek help for their ED, were more likely to hold less positive help-seeking attitudes, and reported seeking help significantly later, than their female or non-ethnic minority (e.g., non-Hispanic Whites, European Americans) counterparts [ 56 , 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another factor that positively influenced help-seeking behaviour among emerging adults was when other aspects of life suffered because of the ED [ 11 ], such as the inability to compete in sport [ 55 ], when their close relationships were affected [ 48 ], and when experiencing emotional distress and health concerns [ 58 ]. On the other hand, greater levels of disordered eating cognitions (e.g., fear of gaining weight), psychological distress and inflexibility, and pleasantness of ED symptoms in comparable samples were conversely found to be associated with less favourable help-seeking attitudes [ 11 , 78 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation